A nickel oxide@nickel–graphene quantum dot self-healing hydrogel for colorimetric detection and removal of lambda-cyhalothrin in kumquat. (3rd May 2022) - Nana, Li; Ruiyi, Li; Wang, Guangli; Haiyan, Zhu; Li, Zaijun
Abstract : The detection and removal of pesticide residues in fruits and vegetables are important to ensure human health, but the current methods face challenges in terms of sensitivity, specificity and convenience of use. Abstract : The detection and removal of pesticide residues in fruits and vegetables are important to ensure human health, but the current methods face challenges in terms of sensitivity, specificity and convenience of use. This study reports the synthesis of a PN junction nickel oxide@nickel–histidine-functionalized graphene quantum dot hybrid (NiO@Ni-His-GQDs) via the coordination of Ni 2+ with His-GQDs and thermal reduction and oxidation in sequence. The hybrid shows a small particle size of about 15 nm, a core–shell structure and a PN junction. This unique structure achieves an improved oxidase-like activity. Furthermore, the hybrid was integrated with PVA to construct a self-healing hydrogel with boric acid as a crosslinking agent. The formed hydrogel can catalyze the oxidation of 3, 3′, 5, 5′-tetramethylbenzidine to produce a blue compound. However, the presence of lambda-cyhalothrin significantly inhibits the oxidase activity and results in a decreased absorbance. The absorbance linearly decreases with increasing lambda-cyhalothrin concentration in the range of 0.75–50 μM with a detection limit of 0.31 μM (S/N = 3). The proposed analytical method provides a better sensitivity and selectivity compared with the reported methods. To remove lambda-cyhalothrin, NiO@Ni-His-GQD gel tablets were stuck to the kumquat surface. These gel tablets extend automatically and rapidly cover the whole surface. The removal efficiency of lambda-cyhalothrin reaches 80% with a retention rate of more than 90% after 10 times of reuse.